Effect of Fish Meal Replacement by Unconventional Meal in the Post-Larval Diet of Clarias Gariepinus in Benin (West Africa) - SOSSOUKPE, EDMOND; Odjo, Isidore N.; GODOME, Théophile; Fiogbé, Emile D. (My University, 2022)
To reduce the pressure on aquatic resources due to the use of fishmeal in fish feed, the mastery and use of alternative sources of fishmeal in all stages of fish development are essential. Five diets including 4 experimental and one control diet were considered. Experimental diets of post-larvae were developed from unconventional ingredients in which fishmeal was completely replaced by a mixture of brewer’s yeast, chicken viscera and maggots. These foods were tested on Clarias gariepinus post-larvae with an initial average weight of 80 ± 1 mg. 1500 fish individuals were equally distributed in 15 concrete basins with a volume of 500 L forming five treatments in triplicate. Fish individuals were fed, manually at a ration rate of 20%, four times per day. The specific growth rates were 8.38%/day in imported food and 6.35%/day in the experimental food receiving 45.5% of protein from unconventional meal. Similar results were obtained with the feed consumption index. These encouraging results show that it is possible to partially or completely replace fishmeal in catfish feed and obtain an economically profitable production. The recovery of waste such as chicken viscera, brewer’s yeast and soybean meal in fish food formulation as tested in this study is a good contribution to environmental sanitation.
Keywords: Maggot Meal; Brewer’s Yeast; Diet; Post-Larvae; Fish Meal Replacement; Benin